2020
DOI: 10.1016/j.psj.2019.10.075
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Evaluation of a heat stress model to induce gastrointestinal leakage in broiler chickens

Abstract: The purpose of this study was to evaluate heat stress as a model to induce gastrointestinal leakage in broiler chickens. On the day of hatch, 320 chicks were allocated into 8 environmental chambers, 4 thermoneutral ( TN ) and 4 continuous heat stress ( HS ). Each chamber was divided into 2 pens containing separate feeders and water jugs (8 replicates per treatment, 20 birds/pen). The environment was established to simulate production setting as best possible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
8
43
0
Order By: Relevance
“…Although the markers mentioned above were not determined in the present study, FITC-d, a large molecule (3-5 kDa) that, under normal intestinal health conditions, does not leak through the epithelium, was used. However, when there is damage to the epithelium, the permeability of FITC-d increases so that it can be quanti ed in serum [55]. In the present study, all treated groups showed lower serum FITC-d concentrations compared to the PC group (Table 2).…”
Section: Discussionsupporting
confidence: 42%
“…Although the markers mentioned above were not determined in the present study, FITC-d, a large molecule (3-5 kDa) that, under normal intestinal health conditions, does not leak through the epithelium, was used. However, when there is damage to the epithelium, the permeability of FITC-d increases so that it can be quanti ed in serum [55]. In the present study, all treated groups showed lower serum FITC-d concentrations compared to the PC group (Table 2).…”
Section: Discussionsupporting
confidence: 42%
“…However, when there is damage to the epithelium, the permeability of FITC-d increases so that it can be quanti ed in serum [55]. In the present study, all treated groups showed lower serum FITC-d concentrations compared to the PC group (Table 2).…”
Section: Discussionsupporting
confidence: 42%
“…In the present study, FITC-d, a large molecule (3-5 kDa) that, under normal intestinal health conditions, does not leak through the epithelium, was used to assess intestinal permeability. However, when there is damage to the epithelium, the permeability of FITC-d increases so that it can be quanti ed in serum [57]. In the present study, all treated groups showed lower serum FITC-d concentrations compared to the PC group (Table 2).…”
Section: Discussionsupporting
confidence: 42%